Depressive Symptoms in the Elderly-An Early Symptom of Dementia? A Systematic Review - Wietse Wiels; Wietse Wiels; Chris Baeken; Chris Baeken; Chris Baeken; Chris Baeken; Sebastiaan Engelborghs; Sebastiaan Engelborghs; Sebastiaan Engelborghs (Frontiers Media S.A., 2020)
BackgroundDepression and dementia are common incapacitating diseases in old age. The exact nature of the relationship between these conditions remains unclear, and multiple explanations have been suggested: depressive symptoms may be a risk factor for, a prodromal symptom of, or a coincidental finding in dementia. They may even be unrelated or only connected through common risk factors. Multiple studies so far have provided conflicting results.ObjectivesTo determine whether a systematic literature review can clarify the nature of the relation between depressive symptoms and dementia.MethodsUsing the Patient/Problem/Population, Intervention, Comparator, Outcome or PICO paradigm, a known framework for framing healthcare and evidence questions, we formulated the question "whether depressive symptoms in cognitively intact older adults are associated with a diagnosis of dementia later in life." We performed a systematic literature review of MEDLINE and PsycINFO in November 2018, looking for prospective cohort studies examining the aforementioned question.ResultsWe critically analyzed and listed 31 relevant papers out of 1,656 and grouped them according to the main hypothesis they support: depressive symptoms as a risk factor, not a risk factor, a prodromal symptom, both, or some specific other hypothesis. All but three studies used clinical diagnostic criteria for dementia alone (i.e., no biomarkers or autopsy confirmation). Several studies contain solid arguments for the hypotheses they support, yet they do not formally contradict other findings or suggested explanations and are heterogeneous.ConclusionsThe exact nature of the relationship between depressive symptoms and dementia in the elderly remains inconclusive, with multiple studies supporting both the risk factor and prodromal hypotheses. Some provide arguments for common risk factors. It seems unlikely that there is no connection at all. We conclude that at least in a significant part of the patients, depressive symptoms and dementia are related. This may be due to common risk factors and/or depressive symptoms being a prodromal symptom of dementia and/or depression being a risk factor for dementia. These causal associations possibly overlap in some patients. Further research is warranted to develop predictive biomarkers and to develop interventions that may attenuate the risk of "conversion" from depressive symptoms to dementia in the elderly.